Docent Borisas Voronkovas (1911–1987) 100 years - Merkys, Vytautas; Uždavinys, Romualdas; Verikaitė, Vitolda (Lietuvos matematikos rinkinys, 2011)
B. Voronkovas life review. Scientific work. Bibliographical listing.